Genotype of UGT1A1 and phenotype correlation between Crigler–Najjar syndrome type II and Gilbert syndrome. Issue 2 (28th January 2016) - Maruo, Yoshihiro; Nakahara, Sayuri; Yanagi, Takahide; Nomura, Akitaka; Mimura, Yu; Matsui, Katsuyuki; Sato, Hiroshi; Takeuchi, Yoshihiro
Abstract: Background and Aims: Hereditary unconjugated hyperbilirubinemias, Crigler–Najjar syndrome type I, Crigler–Najjar syndrome type II (CN‐2), and Gilbert syndrome (GS) all result from mutations of the bilirubin uridine 5'‐diphosphate (UDP)‐glucuronosyltransferase gene ( UGT1A1 ). Often, to distinguish between CN‐2 and GS is difficult because the borderline of the two syndromes is unclear. We analyzed the genotypes and phenotypes of 163 Japanese patients with CN‐2 or GS. Methods: Japanese patients (99 males and 64 females) with unconjugated hyperbilirubinemia were analyzed. Their serum bilirubin concentrations varied from 1.2 to 22.2 mg/dL (20 to 379 μM). Genetic analysis of UGT1A1 was performed by PCR‐amplified direct sequencing. Association between serum bilirubin concentrations and genotypes group (typical CN‐2, intermediate group, and typical GS) was studied. Results: Most patients had biallelic mutations of UGT1A1 . Moreover, many of them (78.5%) had multiple mutations. The mutation in typical CN‐2 was a homozygous double missense mutation of p.[G71R:Y486D]. In typical GS group, four prevalent genotypes were detected: homozygous UGT1A1 * 28, UGT1A1 * 6 / UGT1A1 * 28, and homozygous UGT1A1 * 6, and UGT1A1 * 27 / UGT1A1 * 28 . In the intermediate group, three genotypes, p.[G71R:Y486D]/ UGT1A1 * 7, p.[G71R:Y486D]/ UGT1A1 * 6, and homozygous UGT1A1 * 7, were detected. Serum bilirubin concentrations of typical CN‐2, intermediate group, and typical GS are respectively 12.9 ± 5.1, 5.2 ± 2.2, and 2.8 ± 1.1 mg/dL. Serum bilirubin concentration among the three groups is statistically different ( P  < 0.0001). Conclusions: The serum bilirubin concentration varied continuously from GS to CN‐2 depending on genotypes. Because of the combination of the mutations and polymorphisms, many patients showed intermediate serum bilirubin concentration between two syndromes. Clinically, it is difficult to distinguish clearly between the two syndromes.